Panorama da pesquisa em Design no Brasil: a contribuição dos Programas de Pós-Graduação em Design nas pesquisas científicas e no desenvolvimento da área - Neves, Erica Pereira das [UNESP] (2014)
With respect to design, scientific production in the area helps consolidate it as a scientific field can contribute to the development of society through the promotion of the construction of critical knowledge of researchers. Scientific conferences and journals, periodicals and books consist of some of the effective actions for the exchange of knowledge. Through these channels the results of research are disseminated, shared and put into discussion, collaborating with the learning process and cooperation among sectors. Thus, this paper reflects on the evolution of scientific research in the area and attempts to give an overview of current research of Design in Brazil and its correlation with the Graduate Program in Design.